2009
DOI: 10.1002/car.1089
|View full text |Cite
|
Sign up to set email alerts
|

Determining the skills for child protection practice: emerging from the quagmire!

Abstract: This paper, the second in a series of two, presents and analyses the results of an extended literature review undertaken for a Master's dissertation, the purpose of which was to establish the evidence base for the learning and teaching of skills for child protection practice. The review, discussed in the previous paper, was carried out in two stages. An initial search yielded a very small number of studies of direct relevance but they provided the trigger and the key words for a second search. Many potentially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…20 An extensive literature review of the skills required to work in child protection demonstrated that managing the emotional impact was not regularly recognised as a crucial part of the process. 23 This supports the experiences of the midwives in our study who agreed that the level of emotional work required was not addressed in the child protection training they had attended.…”
Section: Discussionsupporting
confidence: 79%
“…20 An extensive literature review of the skills required to work in child protection demonstrated that managing the emotional impact was not regularly recognised as a crucial part of the process. 23 This supports the experiences of the midwives in our study who agreed that the level of emotional work required was not addressed in the child protection training they had attended.…”
Section: Discussionsupporting
confidence: 79%
“…Official rates of child maltreatment indicate less than a tenth of other estimates (Gilbert et al ., , ), and also that there is a lack of awareness both of the signs of child maltreatment and of the processes for reporting it. Appleton () and Keys (, ) also stress the need for improving the quality of recognition and intervention practices. Strategies to improve recognition and evidence‐based guidelines should be created in different countries, as has been done in the UK (Appleton and Glaser, ).…”
mentioning
confidence: 99%
“…This links to Keys' () use of the concept of pro‐social modelling which takes place through the manner in which professionals behave and interact. This role‐modelling creates an unspoken set of ground rules, and in cases of good practice seeks to imply respect and courtesy toward the person and his\her feelings.…”
Section: Work With Fathers and Families Pre‐conferencementioning
confidence: 92%